Replicated optical microstructures in hybrid polymers: process technology and applications - Obi, Samuel (My University, 2006)
This thesis reports the design, fabrication and testing of new microstructures made in inorganic-organic hybrid polymers. Sol-Gel materials of the ORMOCER® brand are such hybrid polymers that combine the properties of ceramics and organic polymers. These materials have a high temperature stability, very good chemical resistance and excellent optical properties, but can be processed by simple UV-casting methods. Low-cost replication technologies like injection molding or hot embossing are known for their high precision in the reproduction of very small features. This property is particularly useful for the manufacturing of micro-optical devices, where accuracies in the nanometer range are needed. In this study, UV-replication processes have been combined with micro-fabrication techniques, such as photolithography and thin-film evaporation, to built microsystems in hybrid polymers. With very few process steps, complex microstructures like cantilever beams incorporating refractive microlenses have been made. High aspect ratios (20 to 1) in structures with feature sizes of 5 micrometers have been achieved with ORMOCER® contact photolithography. One application of this microfabrication technology with inorganic-organic hybrid polymers is the assembly of microsystems with clipping structures. Two designs of microscopic clips have been developed and tested. Both types of clipping devices consist of two complementary (male and female) parts with a footprint of less than 1 by 1 mm. The clipping structures are capable of generating 100 mN of holding force per square millimeter. This assembly method is reversible; it has been demonstrated that the clips can be separated and engaged again without loss of retaining force. The assembly of microsystems by clipping is a promising approach: Clipping is fast and cost-effective, because no temperature cycles are required. Pieces attached by clipping can be removed from the microsystem if needed, for example to replace broken or contaminated parts or to increase the yield in a production process. Arrays of clipping structures are expected to multiply the holding forces and to improve the precision. Potential applications of this technology include modules for optical communication devices, illumination systems, miniaturized cameras and sensors, and biomedical microsystems.
Thèse de doctorat : Université de Neuchâtel, 2006 ; 1878